Discrete optimization and operations research : 9th International Conference, DOOR 2016, Vladivostok, Russia, September 19-23, 2016, Proceedings /: 9th International Conference, DOOR 2016, Vladivostok, Russia, September 19-23, 2016, Proceedings. (2016) - Unknown
No abstract available